Historical Contribution of Islamic Waqf in Human Capital Development through Funding Education - Khan, Muhammad Tariq; Khan, Shiraz; Khan, Muhammad Hayat (Journal of Islamic and Religious Studies, 2018)
Islam being a complete code of life encompasses all aspects of a person’s personal and social life. Islam considers those as Muslims who submit to the will of Allah Almighty in all aspects of life. Islam is not merely a matter of private life and its worship system is not restricted only to a set of rituals, but has pervasive social consequences and develops a strong sense of moral society based on system of rules around center of universal concept of justice. Therefore, Islam proposed institutions with relation to justice, governance, cooperation and solidarity for achieving high economic growth and development. Achievement of development and growth of economy is fast in a society or country if it has developed human capital (human resource). Human capital is developed when education is imparted and facilities of health and sound life are provided to human beings. According to Islamic principles, if human beings cannot afford proper education in the society (or other facilities such as health care) then those who are well off endow their properties in Zakat, Awqaf (plural of waqf) and Charities for their better development and nourishment. These properties when endowed as Awqaf are deployed for propagation of education (knowledge, skills, training etc.) by establishing Madrassas (schools, maktabs, colleges, universities etc.) libraries, translating books, and conducting research. In Islamic society there were many Awqaf founded for establishing Madrassas. This paper is dedicated to discuss the development of human capital through education funded by Islamic Awqaf by reviewing literature.